Rhetorical Examination of Research Articles: Macrostructure, Cyclic Moves, Citations and Possible Cultural Influences - Loi, Chek Kim; Soon, Chiow Thai; Siti Katijah Johari (2019)
This paper investigates the rhetorical patterns of the introduction sections of English and Chinese research articles. The paper adopts Swales’s (1990) framework of move analysis. In this study, the cyclic moves are looked into. In addition, citation analysis which serves as a complementary analysis is undertaken to further reveal the distinctive rhetorical characteristics in the two sets of introductions. The citation analysis uses Swales’s (1990) categorization of citations (i.e. integral and non-integral). In general, the findings of the present study reveal that both sets of data employ the similar macrostructure. On the other hand, the recycling of different moves and steps occurs more frequently in English than in Chinese introductions. In addition, there is a disparity between the occurrences of citations in English and Chinese introductions. However, both sets of data show a preference for nonintegral compared to integral citations. Some possible Chinese cultural influences on the rhetorical patterns employed in the selected Chinese research article introductions are also discussed. The present study has pedagogical implications.